2005
DOI: 10.1242/jcs.01657
|View full text |Cite
|
Sign up to set email alerts
|

Raf/MEK/MAPK signaling stimulates the nuclear translocation and transactivating activity of FOXM1c

Abstract: The forkhead box (FOX) transcription factor FOXM1 is ubiquitously expressed in proliferating cells. FOXM1 expression peaks at the G2/M phase of the cell cycle and its functional deficiency in mice leads to defects in mitosis. To investigate the role of FOXM1 in the cell cycle, we used synchronized hTERT-BJ1 fibroblasts to examine the cell cycle-dependent regulation of FOXM1 function. We observed that FOXM1 is localized mainly in the cytoplasm in cells at late-G1 and S phases. Nuclear translocation occurs just … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
170
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(181 citation statements)
references
References 35 publications
6
170
1
Order By: Relevance
“…We found that 59.3% of the investigated Hcc samples showed positive FoXM1 expression compared with 23.8% of FoXM1-positive non-tumorous tissues, suggesting that overexpression of FoXM1 occurred in human Hcc tumors. Moreover, nuclear staining pattern of FoXM1 was observed exclusively in Hcc tissues, indicating that FoXM1 signaling was more active in tumor cells since nuclear translocation of FoXM1 is required to maximally exert its transcriptional function (11,26). this interpretation is further supported by our finding that FOXM1 expression in HCC was closely correlated with tumor proliferation reflected by nuclear pcnA expression.…”
Section: Discussionsupporting
confidence: 71%
“…We found that 59.3% of the investigated Hcc samples showed positive FoXM1 expression compared with 23.8% of FoXM1-positive non-tumorous tissues, suggesting that overexpression of FoXM1 occurred in human Hcc tumors. Moreover, nuclear staining pattern of FoXM1 was observed exclusively in Hcc tissues, indicating that FoXM1 signaling was more active in tumor cells since nuclear translocation of FoXM1 is required to maximally exert its transcriptional function (11,26). this interpretation is further supported by our finding that FOXM1 expression in HCC was closely correlated with tumor proliferation reflected by nuclear pcnA expression.…”
Section: Discussionsupporting
confidence: 71%
“…FoxM1 expression increases during the G1 to S phase after cyclin E/cyclin-dependent kinase 2-mediated (Major et al, 2004) and Ras/Mek/Erk kinase-mediated phosphorylation (Ma et al, 2005). However, it is unlikely that the increase in G1-phase cells and downregulation of FoxM1 expression in response to OGT knockdown is due to loss of Mek/Erk signaling, as no decrease in Erk activation is observed in OGT knockdown cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TP53 mutations induce an increase in FOXM1 expression and subsequent abnormal signaling (33). Three isoforms of FOXM1, FOXM1c, FOXM1b and FOXM1s, are involved in cell proliferation and DNA repair (34,35), and the effects of TP53 genetic mutations on these signaling molecules have been hypothesized to cause malignant transformation in cells (36).…”
Section: Genomic Analysis In Ovarian High-grade Serous Carcinomamentioning
confidence: 99%